Study of Efficiency Fractal Optical Modulator for insulator material by testing modulation transfer function - L. Jabbar, Mohammed; Shwya Alwan, Abbas (University of Thi-Qar Journal of Science, 2017)
Chopper is an important component in optical system. It represents a device, which changes the angle between the coordinate and vision lines of the target for the electrical signal. The chopper modulates the optical signal by a frequency dependent on the number and sectors shapes. The optical modulator takes shapes of various circular due to the need for it. Through this study we have designed the fractal optical modulator its two circles inner and outer, each circle involving in eighteen sectors, by building a computer program using visual basic language. In this paper, we assume that nine sectors one opaque and the other nine sectors are transmitted for the light. Even though the importance of the modulation transfers function (MTF) in testing and evaluating optical systems, it becomes the dependent measurement to know efficiency of the optical systems. It has been studied for optical systems at circular apertures, where that function could evaluate the image efficiency for point object in image planes at different magnitude of a radius and time. The fractal reticle have been designed of insulator material by using the fractal function. Then , evaluating the values of MTF at different values of a radius and time. Also we studied relation between number of sections and spatial frequency.